Gamma-aminobutyric acid promotes human hepatocellular carcinoma growth through overexpressed gamma-aminobutyric acid A receptor α3 subunit - Liu, Yan (The WJG Press and Baishideng, 2008)
AIM: To investigate the expression pattern of gamma-aminobutyric acid A (GABAA) receptors in hepatocellular carcinoma (HCC) and indicate the relationship among gamma-aminobutyric acid (GABA), gamma-aminobutyric acid A receptor α3 subunit (GABRA3) and HCC. METHODS: HCC cell line Chang, HepG2, normal liver cell line L-02 and 8 samples of HCC tissues and paired non-cancerous tissues were analyzed with semiquantitative polymerase chain reaction (PCR) for the expression of GABAA receptors. HepG2 cells were treated with gamma-aminobutyric acid (GABA) at serial concentrations (0, 1, 10, 20, 40 and 60 μmol/L), and their proliferating abilities were analyzed with the 3-(4, 5-methylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, cell doubling time test, colon formation assay, cell cycle analysis and tumor planted in nude mice. Small interfering RNA was used for knocking down the endogenous GABRA3 in HepG2. Proliferating abilities of these cells treated with or without GABA were analyzed. RESULTS: We identified the overexpression of GABRA3 in HCC cells. Knockdown of endogenous GABRA3 expression in HepG2 attenuated HCC cell growth, suggesting its role in HCC cell viability. We determined the in vitro and in vivo effect of GABA in the proliferation of GABRA3-positive cell lines, and found that GABA increased HCC growth in a dose-dependent manner. Notably, the addition of GABA into the cell culture medium promoted the proliferation of GABRA3-expressing HepG2 cells, but not GABRA3-knockdown HepG2 cells. This means that GABA stimulates HepG2 cell growth through GABRA3. CONCLUSION: GABA and GABRA3 play important roles in HCC development and progression and can be a promising molecular target for the development of new diagnostic and therapeutic strategies for HCC.